Studying Hybridity In Arundhati Roy's : The God Of Small Things - Shoobie, Mostafa Azizpour (2010)
By termination of colonial times, an underlying aspect of independence gained attention: cultural. Many literary scholars and authors began to produce literature and theories which aimed to reflect the experiences of the people before, during, and after colonies. This phenomenon, often called ‗postcolonial literature‘ touches upon several issues and themes. Hybridity is a purportedly hot commodity and a cynosure for many a man of letter in postcolonial literature and criticism. Traces of this outlook could be found in writers such as Salman Rushdie, Jean Rhys, Sara Suleri, and Arundhati Roy whose work responds to the multicultural awareness of their societies. This study focuses mainly on Arundhati Roy‘s 1997 novel, The God of Small Things. A pre-independence Indian saga, it adeptly conceptualizes hybridity and the tension it precipitates from three interrelated perspectives: cultural, social, and individual. Marrying theoretical propositions by Bhabha and Bakhtin, the current study intends to research into the life of peoples as reflected in the novel. It will exploit the possibilities of fusion between cultures, social castes, and individuals and will try to determine what occurs afterwards.